2019
DOI: 10.1371/journal.pone.0226809
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a savings-led family-based economic empowerment intervention for AIDS-affected adolescents in Uganda: A four-year follow-up on efficacy and cost-effectiveness

Abstract: BackgroundChildren who have lost a parent to HIV/AIDS, known as AIDS orphans, face multiple stressors affecting their health and development. Family economic empowerment (FEE) interventions have the potential to improve these outcomes and mitigate the risks they face. We present efficacy and cost-effectiveness analyses of the Bridges study, a savings-led FEE intervention among AIDS-orphaned adolescents in Uganda at four-year follow-up.MethodsIntent-to-treat analyses using multilevel models compared the effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 37 publications
2
27
0
Order By: Relevance
“…Where the same intervention and outcomes were reported multiple times, only one paper was included in the analysis. There were six papers generated from the Bridges to Future Intervention in Uganda, [34][35][36][37][38][39] including one paper by Tozan et al, 39 which summarised all results from the previous papers, and thus was the only one included in the analysis. Two papers reported on Kenya's Cash Transfer Programme for Orphans and Vulnerable Children 40 41 and both reported the same outcomes in adolescents.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Where the same intervention and outcomes were reported multiple times, only one paper was included in the analysis. There were six papers generated from the Bridges to Future Intervention in Uganda, [34][35][36][37][38][39] including one paper by Tozan et al, 39 which summarised all results from the previous papers, and thus was the only one included in the analysis. Two papers reported on Kenya's Cash Transfer Programme for Orphans and Vulnerable Children 40 41 and both reported the same outcomes in adolescents.…”
Section: Resultsmentioning
confidence: 99%
“…45 The key details of each study are listed in table 1. Overall, the included studies involved 43 861 participants from Latin American or African regions: two in Mexico, 42 43 Malawi 45 46 and Kenya, 40 47 and one in Uganda, 39 Liberia, 48 Ecuador, 49 Nicaragua, 50 South Africa 51 and Cambodia. 52 All studies were published in 2007 or later.…”
Section: Resultsmentioning
confidence: 99%
“…Findings indicate that the CDAs helped parents of children in the treatment group maintain high expectations for their children's education (66), reduced the intensity of maternal depressive symptoms (57), reduced punitive parenting practices (55), and improved children's early social-emotional development (56). Other studies conducted in sub-Saharan Africa have found that a CDA intervention improved mental health functioning for children and caregivers (e.g., 47,63,118,122) and reduced intentions to engage in sexual risk-taking behavior (78,111). Overall, findings suggest that CDAs enable disadvantaged families to build long-term savings and achieve positive health outcomes.…”
Section: Child Development Accounts: a Step Toward Universal Basic Assetsmentioning
confidence: 96%
“…Despite efforts to test the cost-effectiveness of cash-transfer programs (35,96,99,112,118) and policies (81,82), a lack of benchmarks and comparisons limits our understanding of whether cash transfers are cost-effective (and how they might become so). Future research should (a) collect cost data, (b) establish cost-effectiveness benchmarks for different health outcomes, and (c) accumulate and compare cost-effectiveness evidence in multiple settings.…”
Section: Cost-effectivenessmentioning
confidence: 99%
See 1 more Smart Citation